Coupling of Solar Energy and Thermal Energy for Carbon Dioxide Reduction: Status and Prospects - Wang, Zhou‐jun; Song, Hui; Liu, Huimin; Ye, Jinhua (Angewandte Chemie International Edition, 2020)
Enormous efforts have been devoted to the reduction of carbon dioxide (CO2) by utilizing various driving forces, such as heat, electricity, and radiation. However, the efficient reduction of CO2 is still challenging because of sluggish kinetics. Recent pioneering studies from several groups, including us, have demonstrated that the coupling of solar energy and thermal energy offers a novel and promising strategy to promote the activity and/or manipulate selectivity in CO2 reduction. Herein, we clarify the definition and principles of coupling solar energy and thermal energy, and comprehensively review the status and prospects of CO2 reduction by coupling solar energy and thermal energy. Catalyst design, reactor configuration, photo‐mediated activity/selectivity, and mechanism studies in photo‐thermo CO2 reduction will be emphasized. The aim of this Review is to promote understanding towards CO2 activation and provide guidelines for the design of new catalysts for the efficient reduction of CO2. A bundle of energy: The coupling of solar energy and thermal energy is a promising strategy to mediate the activity and/or selectivity of CO2 reduction. The status and prospects of this topic are reviewed, with the aim of providing guidelines for the design of new catalysts.